Studi Kasus Inspeksi 4000 Jam pada Mesin Instrument Air Compressor (IAC) Atlas Copco ZR 75 Unit 2 di PT PLN Indonesia Power UBP Suralaya - Julian Muhammad Zaky; Hamid Abdillah; Rakhmawan Rakhmawan (Pengelola Jurnal Politeknik Negeri Ketapang, 2025)
Periodic inspection of the Instrument Air Compressor (IAC) plays a crucial role in ensuring the smooth operation of power plants. This study evaluates the results of a 4,000-hour inspection of the Atlas Copco ZR 75 unit at PT PLN Indonesia Power UBP Suralaya. The methods used include visual inspection, process parameter monitoring (pressure, temperature, and flow), vibration analysis, and lubricant condition assessment. The findings indicate a decrease in volumetric efficiency due to increased differential pressure across the filters, bearing wear indications, and oil contamination exceeding the manufacturer’s threshold. The main recommendations are to replace filtration elements, clean the intake line, and inspect the bearings. The integration of periodic inspection with condition monitoring has proven effective in improving maintenance performance and minimizing downtime risk.